Life history, mating dynamics and the origin of parental care - Azad, T; Alonzo, SH; Bonsall, MB; Klug, H (Wiley, 2021)
Parental care, mating dynamics and life history co-evolve. Understanding the diversity of reproductive patterns found in nature is a major focus of evolutionary ecology research. Previous research suggests that the origin of parental care of eggs will be favoured when egg and adult death rates and juvenile survival are relatively high. However, the previous research that explored the link between care and life history did not account for among-species variation in mating dynamics. As mating dynamics are generally expected to influence care, we explore, theoretically, the life-history conditions (stage-specific rates of maturation and survival) that favour parental care across three mating scenarios: reproductive rate (1) is unaffected by males (assuming that some males are present), (2) increases as male abundance increases or (3) decreases as male abundance increases. Across scenarios, all forms of care were most strongly favoured when egg and adult death rates, juvenile survival and female egg maturation rates were relatively high. When reproductive rate was unaffected by male abundance or increased as male abundance increased, as we might expect in systems in which females are mate-limited, all forms of care were most strongly favoured when male egg maturation rate (i.e. the rate at which male eggs develop, mature and hatch) was moderate or high. When greater male abundance inhibited reproduction, which might occur in systems with intense male–male competition, all forms of care were most strongly favoured when male egg maturation rate was low-to-moderate. These results suggest that life history affects the evolution of parental care, and sex-specific life history can interact with mating dynamics to influence the origin of care.